2020
DOI: 10.1021/acsami.0c16471
|View full text |Cite
|
Sign up to set email alerts
|

Reusable Filters Augmented with Heating Microfibers for Antibacterial and Antiviral Sterilization

Abstract: Numerous threats to human health and ecosystems on earth exist due to air pollution and the spread of fatal diseases. Airborne pollutants and particulate matter (PM) pose serious public health risks. In addition, the emergence and spread of bacterial and viral diseases constantly threaten public health and safety. Although various approaches have been implemented thus far to protect humans from air pollution and exposure to diseases, several challenges remain to be addressed. In this study, we developed a hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…The main issues in the mentioned process are the resulting micron‐diameters and higher basis weights. [ 114 ] Several coating materials have been reported as copper, [ 115 ] aluminum, [ 114 ] titanium, zirconium, aluminum nitride, among others. [ 29 ]…”
Section: Esnfms Classification For Pm Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main issues in the mentioned process are the resulting micron‐diameters and higher basis weights. [ 114 ] Several coating materials have been reported as copper, [ 115 ] aluminum, [ 114 ] titanium, zirconium, aluminum nitride, among others. [ 29 ]…”
Section: Esnfms Classification For Pm Filtrationmentioning
confidence: 99%
“…This hybrid air filter holds great promise for antibacterial and antiviral protection. [ 115 ] A tree‐like AgNPs/PVDF nanofiber membrane was developed, where the addition of AgNPs did not change the hydrophobic property of the membrane and the filtration efficiency was 99.95–99.97% and the pressure drop was 137.5 Pa; the bacterial reduction rates value against for Staphylococcus aureus and E. coli were kept at a level of higher than 99.6% after exposure to sunlight for 2 weeks. [ 98 ] Likewise, Ag/PAN electrospun fibers deposited on a nonwoven substrate were reported as air filters to remove nanoparticles from the air and also showed bactericidal activity.…”
Section: Esnfms Classification For Pm Filtrationmentioning
confidence: 99%
“…In another advanced strategy, a hybrid and reusable Cu/PAN‐based filter composed of three layers was developed for potential application in face masks. [ 95 ] The three layers are shown in Figure 16 b , c consist of i) the air filtration layer, made by the electrospinning of PAN solution in DMF, for the removal of airborne pollutants and particulate matter (PM), bacteria, or viruses from breathing stream, ii) the heating layer, made by electroplating of Cu on the PAN nanofiber mat, responsible for the production of high heat for deactivation of bacterial and virus particles, and iii) the thermal insulation layer made of polytetrafluoroethylene for preventing the heat from transferring to the other side of the filter and avoiding the burning of the human skin. This three‐layer filter could be simply embedded into the structure of face masks to generate high local temperatures in response to weak voltages to kill the microorganisms (Figure 16d ).…”
Section: Modification Of Masksmentioning
confidence: 99%
“…Increasing evidence demonstrated that microfiber carry bacteria/virus 50 , which may play an important role in their interaction with the host. Intriguingly, compared to normal tissue, GGNs harbored a distinct lung bacterial community structure, with significantly increasing Firmicutes and Bacteroidetes [51][52][53] .…”
Section: Microfibers and The Etiology Of Ggnsmentioning
confidence: 99%